(untitled) (Bangladesh Rice Journal, 2026)
The experiment was conducted at Bangladesh Rice Research Institute (BRRI) regional station farm, Habiganj, in Boro 2016-17 to observe the effect of integrated nutrient management (INM) on growth, yield, yield parameters and nutrient uptake of BRRI dhan29 in the haor soil. The experimental field belongs to the Azmiriganj series, under the agro-ecological zone ‘Sylhet Basin’ (AEZ-21). The experiment was designed with six treatments, including T1 = Fertilizer control, T2 = Recommended chemical fertilizer dose (N-P-K-S-Zn @ 130-18-60-13-4 kg ha-1, respectively), T3 = Cowdung (CD) @ 2 t ha-1 + 50% recommended chemical fertilizer, T4 = CD @ 3 t ha-1 + 50% recommended chemical fertilizer, T5 = CD @ 4 t ha-1 + 50% recommended chemical fertilizer, and T6 = 120% of recommended chemical fertilizer dose. The experiment was laid out in an RCB design with 3 replications using the test crop BRRI dhan29. Application of CD @ 2, 3 or 4 t ha-1 with 50% recommended chemical fertilizer did not exceed the grain yield, yield parameters and nutrient uptake over recommended sole chemical fertilizers. The recommended dose of chemical fertilizer performed better than INM treatments in terms of yield and nutrient uptake in the haor area of the BRRI Habiganj farm. Bangladesh Rice J.28(2): 99-106, 2024